(untitled) (Hoboken, N.J., 2007)
The Encyclopedia of Polymer Science and Technology, Concise Third Edition provides the key information from the complete, twelve-volume Mark's Encyclopedia in an affordable, condensed format. Completely revised and updated, this user-friendly desk reference offers quick access to all areas of polymer science, including important advances in nanotechnology, imaging and analytical techniques, controlled polymer architecture, biomimetics, and more, all in one volume.
Keywords: Plastics,Polymers,Polymerization,Chất dẻo,Hợp chất cao phân tử,Sự trùng hợp (Hóa học)